Liquid structures: A novel Computational Fluid Dynamics (CFD) inspired metamaterial. (January 2021) - Gallina, Paolo; Gei, Massimiliano; Scalera, Lorenzo; Seriani, Stefano
Abstract: We present a theoretical framework for new structural metamaterials we refer to as liquid structures : a topology of bistable mechanisms made up of a high number of cells that are sub-mechanisms composed of pseudo-rigid links and joints. The name liquid structures comes from the similarities they present with the kinematics of the constant flow of incompressible fluids they are inspired by in a limited domain. The layout of the cells are obtained through a two-step process where: (i) the node displacements are computed by means of a Computational Fluid Dynamics tool feeding and (ii) the kinematic synthesis of each cell that is subsequently performed. We report two illustrative examples where star- and diamond-type cells are employed. The paper concludes with a detailed discussion about future theoretical and manufacturing challenges arising from this new metamaterial paradigm.